Effect of PEI Impregnation on the CO2 Capture Performance of Activated Fly Ash. (July 2017) - Dindi, Abdallah; Quang, Dang Viet; Nashef, Enas; Zahra, Mohammad R.M. Abu
Abstract: In the bid to develop cheaper adsorbents for CO2 capture applications, this work investigates the impact of polyethylenimine (PEI) impregnation on the performance of an activated fly ash material for CO2 capture. The fly ash was activated by fusing with NaOH and then subjecting to hydrothermal treatment to derive more porous zeolitic phases which were subsequently loaded with Polyethylenimine (PEI) using a wet impregnation technique. Two different PEI amines (MW∼600 and MW∼1200) were tested at varying concentrations (15%, 20%, and 25%) to study the effect of molecular weight of the PEI as well the loading percentage on the adsorption performance. The activation resulted in a significant increase in surface area from 11 m 2 /g in the fly ash to 270 m 2 /g in the activated fly ash, while the 25% PEI-600 sorbent was found to be the most efficient, giving the highest adsorption capacity of 26 mg/g adsorbent at 70 o C.